Functional cerebral asymmetry for verbal stimuli in a foreign language - Mildner, Vesna (1999)
Ear advantage as an indicatior of functional cerebral asymmetry for verbal stimuli in a foreign language (English) was studied by means of a dichotic listening test and lateralization indices, calculated from the order and accuracy of repetition, on a sample of 55 female right-handers, native speakers of Croatian. Possible effects of the attended ear were controlled. The results suggest left hemisphere dominance in processing foreign-language verbal material, expressed as significant right-ear advantage during divided attention and greater left-hemisphere control when attention effects are taken into consideraton.
Projekt MZOS
ENG